Synthesis and Characterization of Some New Quinolinic acid Derivatives - Haneen Nazar Wahab Al-Issawi (Journal of Global Pharma Technology, 2016)
Preparation of some non-homogeneous cyclic compounds starting with Quinolic acid .A different N-heterocyclic substituted derivative of quinolone has been synthesized. The nitrogen atoms have been alkylated first to form N-carboxymethyl followed by cyclization reaction to form heterocyclic/substituted aryl groups. All the synthesized compounds have been identified using FT-IR, 1H NMR spectrum.Keywords: Quinolinic acid, 1, 3-Oxazole, Imidazol, 1, 2, 4-Triazole, 1, 3, 4- thiadiazol, diazetidin, diazepines.